Development of Information Literacy from the Period of Rasulullah to Khulafaur Rasyidin - Merdekawati, Nur Rahmah; Syam, Kadri Ariski; Mathar, Muh. Quraisy (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2025)
Background of the study: Islamic civilization underwent a significant transformation from an oral tradition society to a literate culture during the time of the Prophet Muhammad and the period of the Khulafaur Rasyidin. This transition represents a crucial development in information literacy that fundamentally shaped Islamic educational and scientific traditions, but comprehensive analysis of this historical evolution remains limited. Purpose: This study aims to examine the development of information literacy from the time of the Prophet Muhammad until the period of the Khulafaur Rasyidin, analyzing how Islamic civilization evolved from an oral tradition into a comprehensive literacy culture that values reading, writing, and the systematic dissemination of knowledge. Methods: The researcher uses qualitative literature research methodology, conducting a systematic analysis of historical sources and Islamic literature to understand the evolution of literacy practices and educational institutions in the early period of Islam. Finding: Re Research indicates that the initial revelation, "Iqra'," established the foundational framework for Islamic literacy culture, which subsequently facilitated the emergence of educational institutions such as Dar al-Arqam, Kuttab, Suffah, and mosques. The Prophet's era was marked by systematic literacy teaching, including an innovative approach that utilized prisoners of war from Badr as teachers. The period of the Khulafaur Rasyidin showed significant progress: the codification of the Quran by Abu Bakar, the expansion of the education system by Umar, the standardization of the language of the Quran by Usman, and the continuation of the scientific tradition by Ali. Islamic literacy culture includes comprehensive information processing skills that go beyond basic reading and writing abilities. Conclusion: The literacy movement initiated during the time of the Prophet and      systematically developed by the Khulafaur Rasyidin established the basic framework for Islamic golden age scholarship and knowledge preservation systems, creating a comprehensive educational culture that significantly influenced world civilization and demonstrated that Islamic information literacy played an instrumental role in developing scientific knowledge and civilizational progress. Keywords: Information Literacy, Islamic Civilization, Khulafaur Rasyidin. ------------------------------------------------------------------------------------------------------------------------------------------------------------------------ Perkembangan Literasi Informasi Masa Rasulullah Sampai Khulafaur Rasyidin Latar Belakang: Peradaban Islam mengalami transformasi signifikan dari masyarakat tradisi lisan menjadi budaya literasi pada masa Nabi Muhammad hingga periode Khulafaur Rasyidin. Transisi ini merepresentasikan perkembangan krusial dalam literasi informasi yang secara fundamental membentuk tradisi pendidikan dan keilmuan Islam, namun analisis komprehensif terhadap evolusi historis ini masih terbatas. Tujuan: Penelitian ini bertujuan untuk mengkaji perkembangan literasi informasi pada masa Nabi Muhammad hingga periode Khulafaur Rasyidin serta menganalisis bagaimana peradaban Islam berevolusi dari tradisi lisan menjadi budaya literasi komprehensif yang menghargai membaca, menulis, dan diseminasi pengetahuan secara sistematis. Metode: Penelitian menggunakan metodologi penelitian literature research melakukan analisis sistematis terhadap sumber-sumber sejarah dan literatur Islam untuk memahami evolusi praktik literasi dan institusi pendidikan pada periode awal Islam. Temuan: Penelitian mengungkapkan bahwa wahyu pertama "Iqra'" menetapkan kerangka dasar budaya literasi Islam, yang mengarah pada pengembangan institusi pendidikan termasuk Dar al-Arqam, Kuttab, Suffah, dan masjid. Masa Nabi ditandai dengan pengajaran literasi sistematis, termasuk pendekatan inovatif memanfaatkan tawanan perang Badar sebagai pengajar. Periode Khulafaur Rasyidin menunjukkan kemajuan signifikan: kodifikasi Al-Quran oleh Abu Bakar, ekspansi sistem pendidikan oleh Umar, standardisasi bahasa Al-Quran oleh Usman, dan kelanjutan tradisi keilmuan oleh Ali. Budaya literasi Islam mencakup keterampilan pemrosesan informasi komprehensif yang melampaui kemampuan membaca dan menulis dasar. Kesimpulan: Gerakan literasi yang diinisiasi pada masa Nabi dan dikembangkan secara sistematis oleh Khulafaur Rasyidin menetapkan kerangka dasar bagi keilmuan masa keemasan Islam dan sistem preservasi pengetahuan, menciptakan budaya pendidikan komprehensif yang secara signifikan mempengaruhi peradaban dunia dan mendemonstrasikan bahwa literasi informasi Islam berperan instrumental dalam mengembangkan pengetahuan ilmiah dan kemajuan peradaban. Kata Kunci: Literasi Informasi, Peradaban Islam, Khulafaur Rasyidin